Generation of subsidies for decision-making in the Brazilian cattle-raising productive chain. - Vicini, Lorena; Souza, Adriano Mendonça (Revista Gestão da Produção Operações e Sistemas, 2007)
The main purpose of this research was to generate statistical subsidies for a policy of incentive to the beef cattleraising in Brazil and from them to insert the beef cattle production in a quality management system, the PDCAcycle. For this purpose some multivariate analysis techniques were used such as, the Cluster Analysis, whichmake possible to group categories of similar beef cattle, considering their production and also to verify the oscillationsoccurred from 1997 to 2000. The Factorial Analysis makes possible to identify the states, which weredistinguished nationally within this period, as well as the regional characteristics, that is, the beef cattle categorypredominant in each state. When identifying the states, which were distinguished nationally, the fat beef cattleprice monitoring was performed in these states x using the time series analysis, this way, forecasting their futureprices. From the states’ identification and their monitoring, the national cattle breeding was inserted into thePDCA cycle, once the stages used to develop this research constitute the stages of the cycle.Keywords: Cattle breeding; Multivariate Analysis; Monitoring; PDCA cycle; Production.